The Romanovs : the final chapter - Massie, Robert K. (New York : Ballantine Books, 1996)
Provides facts and information about the Romanovs, the slain family of the last Russian tsar, the claims by some that Anna Anderson was really the Grand Duchess Anastasia, and the results of forensic tests on the skeletons found in a shallow grave in Siberia.
I. The bones. Down twenty-three steps ; Approved by Moscow ; Let me find nothing ; A character from Gogol ; Secretary Baker ; Curious about death ; The Ekaterinburg Conference ; At the frontiers of knowledge ; Dr. Maples versus Dr. Gill ; Ekaterinburg confronts the past ; Investigator Soloviev ; Burying the Tsar. -- II. Anna Anderson. The imposters ; The claimant ; A matter of family honor ; These people have no standing ; As good as the people using it ; The cleverest of the four children. -- III. The survivors. The Romanov emigres. -- IV. The Ipatiev House. Seventy-eight days.
Keywords: Nicholas II, Emperor of Russia -- 1868-1918 -- Assassination -- Family; Forensic osteology -- Russia; Pretenders to the throne -- Russia; Russia -- History -- 1894-1917